Kekuatan Tekan Restorasi Sandwich Berbasis Semen Ionomer Kaca (Sik) Fuji® II dan Fuji® IX - Sri Lestari (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2012)
The need for esthetic on the desirable dental restoration of patients in dental refunctioning is highly improving, both anterior teeth and posterior teeth. Thus, the use of restoration material applied should meet the esthetic, be able to accept mastication load and to prevent secondary caries. To meet those requirements, sandwich restoration using combination material of composite resine and glass ionomer cement can become a choice. Many kinds of glass ionomer cement that can be used as that restoration basis. The purpose of this study was to observe the pressure strength of sandwich restoration based on the glass ionomer cement Fuji® II and Fuji® IX. The samples were sandwich restoration simulations made using round plastic ring cast with diameter of 5 mm, and thickness of 3 mm. A number of 16 rings were fixed using brass plate, 8 rings for sandwich restorasion based on glass ionomer cement Fuji® II and 8 rings for sandwich restorasion based on glass ionomer cement Fuji® IX. Powder and liquid glass ionomer cement were mixed up to be consistently-thick-and-shiny and subsequently inserted into the rings as thick as 1 mm, condensed and allowed to set for 15 minutes. It was then etched, bonded and applied using ligth activated composite as thick as 2 mm, lightened for 40 seconds. The restoration materials that had been set were then taken out from the rings and subsequently tested for their pressure strength using Autograph Szimadzu (Japan). The result of the study showed that the mean of pressure strength of the sandwich restoration based on glass ionomer cement Fuji® IX (56,80 kgf/cm2) was greater than the sandwich restoration based on glass ionomer cement Fuji® II (16,92 kgf/cm2). The Data was analyzed using Mann Whitney test, and it showed significant difference. It is concluded that restoration based on glass ionomer cement Fuji® IX is capable to endure masticating load greater than the sandwich restoration based on glass ionomer cement Fuji® II.